Операция "Хаос"; Операция "Луна" : фантаст. романы / П. Андерсон - Андерсон Пол (Мастера фантастики, 2003)
Экземпляры: ф.13 (2005) / Инвентарный номер: 49323 / Цена: / Сис.шифр: 84(7Сое) / Авт.знак: А 65 / ГРНТИ: 17.82.31 / ББК: 84(7Сое)